1990
DOI: 10.1016/1044-0305(90)80005-8
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and quantification of ion images with a camera-based detection system and classical quantification algorithms

Abstract: The quantitative analytical characteristics of a camera-based detection system for secondary ion microscopy are studied in detail. Through multiple exposures, ion images with large dynamic ranges are obtained. The quantification of these images by the sensitivity factor method and the matrix ion species ratio method is described and evaluated by the analysis of steel and aluminum standard reference materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The combination of imaging and depth profile technique allows the measurement of three-dimensional distributions of trace elements in material [3,4]. For this purpose the lateral distribution of the elements of interest are registered in each cycle of a depth profile and saved to hard disk.…”
Section: D-distributionsmentioning
confidence: 99%
“…The combination of imaging and depth profile technique allows the measurement of three-dimensional distributions of trace elements in material [3,4]. For this purpose the lateral distribution of the elements of interest are registered in each cycle of a depth profile and saved to hard disk.…”
Section: D-distributionsmentioning
confidence: 99%
“…Adams and colleagues critically examine the determination of sample heterogeneity, and the experimental uncertainties involved, in a pair of studies on the subject (117,118)) image analysis and computer simulations were incorporated to develop and test their sampling constant model. The same research group also reported on the analytical aspects of ion imagery using SIMS and demonstrated applications of their camera-based detection system for steel and A1 samples (119).…”
Section: Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…Secondary ion mass spectrometry (SIMS) exhibits an unique potential for this task: laterally resolved secondary ion signals can be measured during sputter removal of the material, thus yielding signals with n chemical (number of masses or elements measured) and three spatial dimensions [1][2][3].…”
mentioning
confidence: 99%